La cualificación de los métodos especiales de investigación en América Latina y el Caribe - Calderón Arias, Emma (2018)
The especial criminal investigation methods constitute criminalistics and proceedings techniques that supports in criminal proceedings based on diligence and investigation actions that deals with necessary elements for the detection and clearing up of delictual and criminal facts entail new forms of criminality. Due to the organized criminality different methods had been included in the wide range of investigative actions within the different legal bodies commissioned in the initial phase of the penal process come destined to develop the objectives to be achieved in the success of their work. The secret agents and the telephone scouts are special tools for the penal investigators as the result of the advantages that they propitiate.